REVITALISASI KAWASAN BRAGA DENGAN KONSEP PEDESTRIAN MALL SEBAGAI WUJUD KAWASAN PUSAKA KOTA BANDUNG - Angga Nugraha; Ahmad Farkhan; Kusumaningdyah Nurul H. (ARSITEKTURA, 2015)
Braga District became the only one that showed a luxurious lifestyle at 1920-1945, especially the elite European people who live in the Hindia Belanda territory.  After that period, Braga District has decreased quality and quantity, such as illegal parking, abandoned buildings, etc. Braga District is need a revitaliation efforts to became economy district and market place for tourists and  try to restore the image of Braga District as lifestyle district in Bandung City. Braga and Bandung City has potencial as a creative economic development in Bandung City will create new economic activities in Braga District. Braga District revitalization efforts must begin with a variety of problem-solving methods. First, case studies is to find out the problems that arise in the Braga District. Second, field studies is to collect data existing in Braga District. Third, literature studies is to collect a theories relating to the revitalization of Braga District. After the analysis that produce adesign concept. Pedestrian mall concept will be applied to add value to pedestrians and the other activities  user to be more comfortable doing activities in the Braga District. Development of the area in the form of an underground mall aiming to increase the economy and community areas in the Braga District who can be filled by the user of creative economic especially in the fashion things. Design of Braga District refers to the 1920-1945 periode that based on the design of the European Architectural style or Art Deco Architectural style that was popular at that time. Old building conservation efforts in Braga district, new facilities and underground mall in design refers to the style of Art deco architecture. As well as the revitalization of the Braga District goal to become a pilot project area of Bandung City heritage, so the protection and preservation of cultural assets can be monitored by all people. Keywords: Braga District, Pedestrian Mall, Revitalization